Hubungan Program Pemberian Makanan Tambahan dengan Ibu Hamil Kekurangan Energi Kronis (KEK): Literature Review - Erna Erna; Misnaniarti Misnaniarti; Haerawati Idris (Citra Delima Scientific journal of Citra Internasional Institute, 2023)
Chronic Energy Deficiency (CED) is a nutritional problem in pregnant women which is still a nutritional problem in the world. Efforts made to improve the nutrition of pregnant women with CED are by providing additional food. Purpose: to determine the relationship between the supplementary feeding program and chronic energy deficiency pregnant women (KEK). Method: this research uses literature review by collecting articles according to the topic and purpose of writing obtained from various journal databases. The study was carried out by analyzing scientific articles obtained from the Google Scholar and Scopus electronic databases with inclusion criteria, 2013-2023, Indonesian and English. The research article analysis technique is in a table format containing the author, title, year, method (design, sample and analysis), and results. Result: the research results obtained 10 articles using the PICO formulation. Based on the 10 research articles obtained, it shows that giving supplementary feeding programs (PMT) to pregnant women with chronic energy deficiency (KEK) has an effect on increasing total energy intake, nutritional status, body weight, increasing upper arm circumference (LILA), decreasing malondialdehyde levels. , lack of vitamin A and babies with KEK mothers who consume PMT are born normally, do not experience LBW (Low Birth Weight Babies). This literature review study is expected to be a reference, especially in the field of public health.